2021
DOI: 10.1080/10717544.2021.1943059
|View full text |Cite
|
Sign up to set email alerts
|

Drug distribution along the cochlea is strongly enhanced by low-frequency round window micro vibrations

Abstract: The cochlea’s inaccessibility and complex nature provide significant challenges to delivering drugs and other agents uniformly, safely and efficiently, along the entire cochlear spiral. Large drug concentration gradients are formed along the cochlea when drugs are administered to the middle ear. This undermines the major goal of attaining therapeutic drug concentration windows along the whole cochlea. Here, utilizing a well-known physiological effect of salicylate, we demonstrate a proof of concept in which dr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This could be because noise-induced damage is relatively less in the low-frequency range than that in the high-frequency area, 51 or because noise-induced vibration of the RWM and OWM may promote the distribution of EGCG@TDNs towards the apical turn (low frequency area). 52 No obvious loss of outer hair cells was observed in our NIHL model (106 dB, 8-16 kHz, 2 h). However, hematoxylin and eosin (H&E) staining demonstrated that acute noise exposure resulted in the loss of spiral ganglion neurons (SGNs, Fig.…”
Section: Characterization Of Egcg@tdnsmentioning
confidence: 62%
See 1 more Smart Citation
“…This could be because noise-induced damage is relatively less in the low-frequency range than that in the high-frequency area, 51 or because noise-induced vibration of the RWM and OWM may promote the distribution of EGCG@TDNs towards the apical turn (low frequency area). 52 No obvious loss of outer hair cells was observed in our NIHL model (106 dB, 8-16 kHz, 2 h). However, hematoxylin and eosin (H&E) staining demonstrated that acute noise exposure resulted in the loss of spiral ganglion neurons (SGNs, Fig.…”
Section: Characterization Of Egcg@tdnsmentioning
confidence: 62%
“…This could be because noise-induced damage is relatively less in the low-frequency range than that in the high-frequency area, 51 or because noise-induced vibration of the RWM and OWM may promote the distribution of EGCG@TDNs towards the apical turn (low frequency area). 52…”
Section: Resultsmentioning
confidence: 99%
“…Several strategies are under investigation to enhance drug entry into the inner ear through the RWM using magnetic fields ( Du et al, 2013 ; Shapiro et al, 2014 ), ultrasound ( Lin et al, 2021 ), RWM microperforations ( Aksit et al, 2021 ), or nanocarriers ( Jaudoin et al, 2021 ). Approaches to overcome or at least decrease intracochlear basal-apical concentration gradients involve the application of RWM low-frequency micro vibrations ( Flaherty et al, 2021 ) or direct intracochlear drug application ( Chen et al, 2005 ; Hahn et al, 2012 ; Ayoob and Borenstein, 2015 ; Plontke et al, 2017 ; Prenzler et al, 2018 ). In a clinical pilot study, an intracochlear catheter was inserted into the cochlea during CI surgery before insertion of the electrode array to deliver triamcinolone acetonide ( Prenzler et al, 2018 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 49 ] Moreover, vibration and agitation speeds are reported to enhance drug dissolution and delivery. [ 50–52 ] Seeger et al. analyzed and tested the early studies conducted by Beyer and Smith on the dissolution rate of tolbutamide (used for the treatment of non‐insulin‐dependent diabetes mellitus), [ 53 ] and the Embil and Torosian studies on enteric‐coated aspirin, [ 54 ] and confirmed the strong effects of increasing vibration on the drug dissolution time at a low agitation speed of 50 rpm.…”
Section: Introductionmentioning
confidence: 99%